Childhood carcinoid tumors: description of a case series in a Brazilian cancer center - Neves, Gustavo Ribeiro (2006)
CONTEXT AND OBJECTIVE: Carcinoid tumors are very rare both in children and adults. About 85% of these tumors develop in the gastrointestinal tract. The objective of the present study was to describe our experience with children treated of carcinoid tumors, and investigate the frequency morphological findings and results. DESIGN AND SETTING: Report on case series, at the Department of Pediatrics of Centro de Tratamento e Pesquisa Hospital do Câncer, São Paulo. METHODS: This was a retrospective analysis of clinical pathological data and outcomes among children (< 18 years old) with carcinoid tumors admitted from January 1, 1990, to December 31, 2001. RESULTS: Nine patients (mean age 12.2 years) were included: six girls and three boys (2:1), all of them Caucasian. In eight cases (89%), the primary tumor site was the appendix and in one (11%) it was the left bronchus. For those with primary tumor in the appendix, the main complaint was abdominal pain, which led to appendectomy. Only one patient underwent right hemicolectomy due to tumor extension into the se- rosa. The patient with bronchial tumor underwent left pneumonectomy. All patients had localized disease and are alive and free of disease. They have had follow-ups lasting from 1 to 11 years (mean of 3.5 years). CONCLUSION: Although the majority of car- cinoid tumors arise from the appendix, these tumors can also occur in other primary sites. Surgical resection at an early stage allows for good prognosis without the need for any adju- vant treatment.